Lembaga Pendidikan Madrasah Diniyah Riyadul Athfal sebagai Alternatif Pendidikan Islam di Desa Mulangsari Kecamatan Pangkalan Kabupaten Karawang - Rika Mutiara Abdillah; Ahmad Junaedi Sitika; Debibik Nabilatul Fauziah (Pendidikan Agama Islam STIT Palapa Nusantara, 2022)
Madrasah Diniyah is one of the religious education institutions on the outside of school that is comprehensively capable of providing Islamic religious education to students. Madrasah Diniyah is a non-formal Islamic education institution whose learning implementation is carried out in the afternoon and its function is as a complement to Islamic education. From the community's need for this type of educational institution, Madrasah Diniyah persists. Although until now Madrasah Diniyah has received little attention from the government, both in terms of budget fulfillment and manpower assistance, the role of Madrasah Diniyah is very important in the education system that must be considered together. Currently the phenomenon that occurs in the community in Mulangsari Village is a lack of understanding of religion. One indicator is that many parents send their children to public schools with minimal religious education. The existence of Madrasah Diniyah Riyadul Athfal in Mulangsari Village is an alternative for Islamic education in the village. This study aims to determine the implementation of Islamic religious education learning at Madrasah Diniyah Riyadul Athfal and to find out the motivation of the people of Mulangsari Village to receive Islamic religious education at Madrasah Diniyah Riyadul Athfal. The type of research used is descriptive qualitative research. Collecting data using observation, documentation and interview techniques. The results of the study indicate that: The implementation of Islamic religious education at Madrasah Diniyah Riyadul Athfal does not only study the Reading and Writing of the Qur'an but also other Islamic subjects. The learning system applied at Madrasah Diniyah Riyadul Athfal uses the classical system where the students are divided into 6 classes. The motivation for the people of Mulangsari Village to prefer to receive Islamic religious education at Madrasah Diniyah Riyadul Athfal is because the learning is organized, the educational background of the Head of Madrasah Diniyah is graduates from Islamic boarding schools, and the location is very strategic so that it is easily accessible by the community.